2021
DOI: 10.1016/j.sintl.2021.100119
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on current COVID-19 detection methods: From lab care to point of care diagnosis

Abstract: Without a doubt, the current global pandemic affects all walks of our life. It affected almost every age group all over the world with a disease named COVID-19, declared as a global pandemic by WHO in early 2020. Due to the high transmission and moderate mortality rate of this virus, it is also regarded as the panic-zone virus. This potentially deadly virus has pointed up the significance of COVID-19 research. Due to the rapid transmission of COVID-19, early detection is very crucial. Presently, there are diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 134 publications
(228 reference statements)
0
36
0
Order By: Relevance
“…False negative cases in PCR-based SARS-CoV-2 detection can be caused by a variety of factors. For starters, during the viral replication cycle, RNA can be degraded due to decreased stability, resulting in viral genome fragmentation in the circulation, which makes RT-PCR-based detection tough [ 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…False negative cases in PCR-based SARS-CoV-2 detection can be caused by a variety of factors. For starters, during the viral replication cycle, RNA can be degraded due to decreased stability, resulting in viral genome fragmentation in the circulation, which makes RT-PCR-based detection tough [ 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the antibody tests for COVID-19 show very low sensitivity as compared to the PCR test [ 34 ]. Due to the presence of a homologous protein present in the sample, a lower titer value of the antibody or low instrumental sensitivity, this method may give false results [ 26 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional components (probe) are added to situate a foundation that hybridized with the complementary cDNA segment for amplification. The single-step Taqman probe allows real-time quantitative monitoring of the PCR cycle [57]. Nucleic acid detection methods include real-time quantification of the viral genome, which depends on targeting specific regions of the viral genome.…”
Section: Covid-19 Detection Methodsmentioning
confidence: 99%
“…The N protein binds to the viral RNA genome and interacts with M and E proteins, which assists the viral RNA packaging, assembly, and budding [55]. Multiple sequence alignment (MSA) revealed that the M, E, and N proteins for BAT-CoV, SARS-CoV, and SARS-CoV-2 are highly conserved and, accordingly, considered as potential drug targets [15,56,57].…”
Section: Taxonomy and Structure Of Sars-cov-2 Virusmentioning
confidence: 99%